Transparansi dan Akuntabilitas Pengelolaan Dana Desa: Studi Kasus di Desa Susukan Kecamatan Susukan Kabupaten Semarang - Joni Anwar; Dyah Palupiningtyas (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to analyze the implementation of transparency and accountability in the management of Village Funds in Susukan Village, Susukan District, Semarang Regency. Using a qualitative approach with a case study design, this research explores not only the formal and procedural aspects but also the substantive dimensions of transparency and accountability. Data were collected through in-depth interviews, participatory observations, document analysis, and focus group discussions, and were analyzed using a thematic analysis approach. The results reveal that the implementation of transparency and accountability still faces various challenges despite the existence of a comprehensive regulatory framework. Information accessibility and compliance with regulations are relatively adequate; however, the timeliness of publication, diversity of publication media, responsiveness to community feedback, and effectiveness of oversight remain suboptimal. Factors influencing the implementation include the regulatory framework, the capacity of village officials, community budget literacy, information technology infrastructure, and local political dynamics. Community participation in oversight is also low due to limited understanding and the absence of effective participation mechanisms. To improve transparency and accountability, a comprehensive strategy is required, encompassing regulatory refinement, institutional capacity building, the utilization of information technology, and the strengthening of community participation. This study makes a significant contribution to the literature on village governance by integrating multiple dimensions and exploring contextual factors.